The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1002/jez.1402480217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two juvenile hormone analogs (R‐20458, RO203600) and three juvenile hormones (JH 1, 2, and 3) on the number and distribution of sensilla on the seventh abdominal tergite in the male German cockroach, Blattella germanica (L.) (Dictyoptera: Blattellidae)

Abstract: Three types of sensilla, s. chaetica B, s. trichoidea, and s. campaniformia were identified on the 7th abdominal tergite of JH-JHA-and acetone (control)-treated adult male Blattella germanica by light and scanning electron microscopy. All contact chemoreceptors (s. chaetica B) and the majority of mechanoreceptors (s. trichoidea) surround the gland openings or cover the tergal modification, which indicates that contact chemoreception and mechanoreception are important in the tergal feeding stage of mating behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…These findings are in agreement with those of Wheeler and Gupta (1987), who reported that treatment with JH caused deformation of the spiculum copulatus, that included various degrees of distortion to the exterior surface and a significant reduction in length. Third, the G1 and G2 cells of treated tergal glands seemed to be arranged in a less orderly fashion within the tissue.…”
Section: Introductionsupporting
confidence: 94%
See 2 more Smart Citations
“…These findings are in agreement with those of Wheeler and Gupta (1987), who reported that treatment with JH caused deformation of the spiculum copulatus, that included various degrees of distortion to the exterior surface and a significant reduction in length. Third, the G1 and G2 cells of treated tergal glands seemed to be arranged in a less orderly fashion within the tissue.…”
Section: Introductionsupporting
confidence: 94%
“…Treatment with JHA has also been shown to cause a reduction in the number of sensilla associated with the tergal gland openings on tergite seven (Wheeler and Gupta, 1988). The research reported here was designed to examine effects of the JH analog pyriproxyfen on tergal gland secretory tissue development, including the structure of secretory cells and the production of tergal gland secretion proteins.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation